Successful vaccination against Boophilus microplus and Babesia bovis using recombinat antigens - P. Willadsen; D. H. Kemp; G. S. Cobon; I. G. Wright (Memorias do Instituto Oswaldo Cruz, 1992)
Current methods for the control of the cattle tick Boophils microplus and the agent of bovine babesiosis, Babesia bovis are unsatisfactory. Effective immunological control of both parasites would have great advantages. However, naturally acquired immunity to the tick is generally unable to prevent serious production losses. A vaccine against the tick, based on a novel form of immunization, is being developed. A protective antigen has been isolated from the tick, characterized and produced as an effective, recombinant protein. A vaccine incorporating this antigen is currently undergoing field trials. In the Australian situation, improved tick control will probably increase endemic instability with respect to B. bovis. Fortunately, a trivalent, recombinant B. bovis vaccine has also been developed. This too is now undergoing pre-registration field trials.